1971
DOI: 10.1002/zaac.19713800310
|View full text |Cite
|
Sign up to set email alerts
|

Schwingungsspektren von Methylpentafluorosilicaten und Normalkoordinatenanalyse des Methylpentafluorosilications

Abstract: Mit 1 Abbildung Inhaltsiibersicht. Von (NH.J2-, Kz-, Rb,-und Cs,[CH,SiF,] wurden die RAMANund IR-Spektren (400-4000 cm-l, z. T. auch 200-400 cm-l) gemessen und die in den Spektren auftretenden Linien bzw. Banden weitgehend zugeordnet. Ferner wurde eine Normalkoordinatenanalyse des [CH,SiF,]"-Ions durchgefuhrt. Mit Hilfe der IR-Spektroskopie wurde ferner die Bestandigkeit der Methylpentafluorosilicate untersucht.A b s t r a c t . The RAMAB and I R spectra (400-4000 cm-l, partly also 200-400 cm-l) of (NH4)2-, K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1971
1971
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 15 publications
1
0
0
Order By: Relevance
“…The calculations show greater bond lengthening of 11−14% in PhSiF 5 2- (3-21G* and 6-31G*), relative to PhSiF 3 . These calculations are in agreement with IR studies which indicate that the force constant of the Si−C bond, as well as of the Si−F bond, in MeSiF 5 2- , is smaller than that in MeSiF 3 . Since NMR studies have shown that Si−C bond cleavage does not occur in these purified compounds under mild conditions, we may therefore conclude that a bond lengthening of about 4−12% is insufficient to cause Si−C bond cleavage in PhSiF 4 - or PhSiF 5 2- under mild thermal conditions.…”
Section: Resultssupporting
confidence: 88%
“…The calculations show greater bond lengthening of 11−14% in PhSiF 5 2- (3-21G* and 6-31G*), relative to PhSiF 3 . These calculations are in agreement with IR studies which indicate that the force constant of the Si−C bond, as well as of the Si−F bond, in MeSiF 5 2- , is smaller than that in MeSiF 3 . Since NMR studies have shown that Si−C bond cleavage does not occur in these purified compounds under mild conditions, we may therefore conclude that a bond lengthening of about 4−12% is insufficient to cause Si−C bond cleavage in PhSiF 4 - or PhSiF 5 2- under mild thermal conditions.…”
Section: Resultssupporting
confidence: 88%